THE SIGNIFICANCE OF THE SYSTEMIC-SYNERGETIC APPROACH IN SOLVING THE ECOLOGICAL PROBLEMS OF THE ARAL SEA REGION (American Journal of Research in Humanities and Social Sciences, 2026)
This article examines the ecological problems of the Aral Sea region through the prism of the systemic-synergetic approach. The Aral Sea crisis is interpreted as a multi-level systemic phenomenon formed as a result of the complex interaction of ecological, economic, social, and demographic factors. Based on the key principles of systemic-synergetic methodology—open systems, self-organization, nonlinearity, bifurcation, and cooperation—the current condition and development prospects of the Aral Sea region are analyzed. Particular attention is paid to the theoretical and methodological foundations of ensuring environmental security, promoting a green economy, and strengthening regional cooperation.